1999
DOI: 10.1016/s0895-7061(98)00262-3
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and determinants of white coat hypertension in mild to moderate hypertension A primary care-based study

Abstract: Most of the previous studies on white coat hypertension were performed in hypertension clinics or academic settings and included relatively small series of patients. Consequently, the prevalence of white coat hypertension in primary care settings and the clinical and epidemiologic characteristics of this subgroup of patients are not well known. We performed this study to estimate the frequency of white coat hypertension in a population of mildly to moderately hypertensive subjects attended in a primary care se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
3
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 31 publications
7
46
3
2
Order By: Relevance
“…Previous studies have associated an increased prevalence of white coat hypertension with female sex, 4,49,50 particularly when measured by a male. 6,51 This review also associated larger white coat effects with female than with male subjects, although the data did not allow unravelling of the interplay between sex of clinician and patient.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Previous studies have associated an increased prevalence of white coat hypertension with female sex, 4,49,50 particularly when measured by a male. 6,51 This review also associated larger white coat effects with female than with male subjects, although the data did not allow unravelling of the interplay between sex of clinician and patient.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Better-treated BP levels could not explain the differences either, because mean SBP and proportion with SBP Ն160 mm Hg were higher in women than in men. However, women generally have white-coat hypertension more often than men, 26,27 and this could weaken the MA-mortality association. Compared with men, the lipid profile in women was more favorable with higher mean HDL level and a lower proportion had known CVD, indicating that women had a generally lower CV risk at baseline than men.…”
Section: Sex Differencesmentioning
confidence: 99%
“…At present, however, it remains a matter of controversy because its risk profile and clinical relevance are not yet completely clear. Some studies have shown that white coat hypertension is not associated with target organ damage, 3-9 clustering of risk factors (eg hypercholesterolaemia, low high-density lipoprotein cholesterol, insulin resistance), [7][8][9][10][11][12][13][14] and adverse cardiovascular outcome. [15][16][17] On the other hand, different results have been obtained in other reports.…”
Section: Introductionmentioning
confidence: 99%